Performa, bobot karkas, dan lemak abdominal ayam broiler yang diberi dedak fermentasi menggunakan ragi tape (Saccharomyces cerevisiae) - Sri Utami; Emy Saelan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aimed to determine the growth of the carcass weight and abdominal fat of broiler fed fermented rice bran using tape yeast (Saccharomyces cerevisiae). This study was carried out in the poultry production shed of the Animal Husbandry Study Program, Faculty of Agriculture, University of Khairun, located in Fitu Village, South Ternate City. One hundred of DOC broiler which consisted of using a Completely Randomized Design (CRD) which concicted of 5 treatments and 4 replications, namely R0 = basal feed (control), R1 90% basal feed + 10% fermented rice bran, R2 = 80% Basal feed + 20% fermented rice bran, R3 = 70% basal feed +30% fermented rice bran, R4 = 60% basal feed + 40% fermented rice bran. The variables observed included ration consumption, body weight gain, carccas weight and abdominal fat. The results showed that the administration of fermented bran using tape yeast (Saccharomyces cerevisiae) showed no significant difference to feed consumption (P>0.05), but body weight gain, feed conversion showed, carcass weight and abdominal fet significant differences (P<0.05). The results of the study can be concluded that giving up to 20% fermented bran can increase the growth of broiler chickens.